Central African Republic Public Expenditure Review : Creating Fiscal Space to Transition Out of Fragility Through Growth and Poverty Reduction - World Bank (Washington, DC, 2013)
This public expenditure review (PER) aims to assist the government in its efforts to achieve a transition out of fragility through growth and development. Higher and sustained per capita real gross domestic product (GDP) growth to raise the income of the population and create employment is needed to reduce poverty and lower the risk of reversion to conflict. Significant productive investments in human capital and in infrastructure are needed to help Central African Republic (CAR) foster and sustain higher economic growth. Thus, the government needs to create fiscal space in the budget to finance its reform program and productive investments in health, education, and infrastructure to spur growth. While the burden of investment should be on the private sector the government has a key role to play in facilitating private investment and in providing the basic infrastructure that the private sector needs as well as public services to the poor. The PER advances the notion that public spending at the appropriate level, allocated to productive areas and used efficiently, will be essential to promote rapid and broad-based economic growth in CAR. More specifically, the PER examines the central question of how to create and use fiscal space in the government budget to support long-term economic growth and poverty reduction in CAR while maintaining macro-fiscal stability.